Mapping asthma-associated variants in admixed populations - Mersha, Tesfaye B. (Frontiers in Genetics, 2015)
Admixed populations arise when two or more previously isolated populations start interbreeding. Mapping asthma susceptibility loci in an admixed population using admixture mapping (AM) involves screening the genome of individuals of mixed ancestry for chromosomal regions that have a higher frequency of alleles compared to the parental population with higher asthma risk. AM takes advantage of the admixture created in populations of mixed ancestry by searching for association between the ancestry score of a marker and asthma, as opposed to that between the genotype of the marker and asthma. The theory behind AM is that chromosomal segments of affected individuals contain significantly higher than average proportion of alleles from the high-risk parental population and thus are more likely to harbor a disease-gene allele(s). Criteria and practical requirements for AM to be feasible include: (1) prevalence of a disease is significantly different between the ancestral populations from which the admixed population was formed; (2) measurable difference in disease-causing alleles between the parental populations; (3) reduced linkage disequilibrium (LD) between unlinked loci across chromosomes and strong LD between neighboring loci; (4) a set of markers with noticeable allele-frequency differences between parental populations contributing to the admixed population. Single nucleotide polymorphisms by being abundant, stable, relatively cheap to genotype, and informative for LD structure of chromosomal segments are the markers choice; and (5) understanding the extent of segmental chromosomal admixtures, and their interactions with environmental factors in the study population. In this review, we summarize the historical context of admixed population and AM, and current opportunities of AM to map asthma genes. In addition, we provide an overview of potential limitations and future directions of AM in biomedical research including asthma and asthma-related disorders.